2015
DOI: 10.1016/j.proeng.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Extracellular Matrix Components Modulates the Phenotype of Human Smooth Muscle Cells in Vitro and Allows for the Control of Properties of Engineered Tissues

Abstract: Smooth muscle cells (SMCs) play a significant role in the pathogenesis of atherosclerosis. 2D cultures elucidated valuable information about the interaction between SMCs and extracellular matrix (ECM) components. However, 3D constructs better represent the native vascular environment. Furthermore, a limited number of studies addressed the effect of ECM stiffness on SMCs phenotype. We investigated the effect of stiffness of different ECM substrates by modulating their concentrations, including the effect on mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…AFM nanoscale characterization demonstrated that gels consisted of collagen fibres exhibiting the characteristic D-band periodicity and had random orientation ( figure 6). As the collagen concentration increased, the gel density, stiffness and collagen fibre diameter were significantly increased, confirming previous research demonstrating that alterations in collagen concentration are translated into changes in ECM stiffness [28,40]. Concerning fibre diameters, we found a range of 50-300 nm, similar to previous studies performed in high concentrated collagen gels [25] and within the range of fibre diameter of native tissues [28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…AFM nanoscale characterization demonstrated that gels consisted of collagen fibres exhibiting the characteristic D-band periodicity and had random orientation ( figure 6). As the collagen concentration increased, the gel density, stiffness and collagen fibre diameter were significantly increased, confirming previous research demonstrating that alterations in collagen concentration are translated into changes in ECM stiffness [28,40]. Concerning fibre diameters, we found a range of 50-300 nm, similar to previous studies performed in high concentrated collagen gels [25] and within the range of fibre diameter of native tissues [28].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we developed 3D collagen models to study cell invasion in a more physiologically relevant approach [40]. In our 3D experiments, we formed tumour cell spheroids that were embedded in collagen gels of different concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A loss of laminin and an increase in fibronectin surrounding smooth muscle cells has been observed during the progression of neointima formation in vascular disease, suggesting these proteins may play an important role in regulation of cell phenotype in disease (39). Additionally, increasing stiffness has been shown to drive smooth muscle cells toward the synthetic, migratory phenotype observed in atherosclerosis (40,41), This evidence that VSMC phenotype is modulated by both matrix stiffness and composition, coupled with our previous observations of matrix typedependent responses to stiffness by VSMCs, led us to hypothesize that the durotactic migratory behavior of VSMC s on substrates with mechanical gradients may also be differentially modulated by fibronectin and laminin.…”
mentioning
confidence: 99%
“…In addition to altered actomyosin activity, matrix stiffness also potentially influences VSMC differentiation. VSMC phenotype is regulated by numerous environmental cues, including the ECM [92] . Atherosclerotic plaques display reduced levels of elastin and collagen-I accumulation [93] .…”
Section: Cvd and The Role Of Matrix Stiffnessmentioning
confidence: 99%